1961
DOI: 10.1146/annurev.bi.30.070161.003321
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of the Dividing Cell

Abstract: The normal form of cell reproduction involves the duplication of the nu clear genetic material, the partitioning of the genetic material into two equiv alent, or "sister," nuclei, and the partitioning of the cytoplasm into two separate cells, each with one of the nuclei, Nuclear division is not necessarily followed by cytoplasmic division ; the production of multinucleated cells is a common occurrence in nature and in experiments. On the other hand, cell division without nuclear division, which would produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 66 publications
(74 reference statements)
1
7
1
1
Order By: Relevance
“…The absence of the centrosome, a structure whose character most likely reflects centriole activity, suggests that, aside from the separatory movement, G 1 is a phase of centriolar quiescence. This discrepancy between our findings and those of Mazia et al (4) are, in all probability, due to the short generation time of their marine eggs compared to the 17 hr life cycle of the HeLa cell.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The absence of the centrosome, a structure whose character most likely reflects centriole activity, suggests that, aside from the separatory movement, G 1 is a phase of centriolar quiescence. This discrepancy between our findings and those of Mazia et al (4) are, in all probability, due to the short generation time of their marine eggs compared to the 17 hr life cycle of the HeLa cell.…”
Section: Resultscontrasting
confidence: 99%
“…Centriole replication by orthogonal budding from a parent centriole has been described in both the light and electron microscopes (1)(2)(3). Its temporal relationship to the telophase stage of the cell cycle has been inferred, in sea urchin, from the morphological modification of cell division induced by mercaptoethanol (4), and Cleveland's extensive work on centriole replication in flagellates is well known (5). In mammalian cells, replication is assumed to occur sometime during interphase; however, the lack of more precise data is due in large part to the dearth of morphological criteria which might distinguish individual segments of interphase.…”
mentioning
confidence: 99%
“…Previous reports have suggested that a withdrawal of ATP supply induces proliferation arrest in the G 1 phase of the cell cycle. 20 Indeed, a recent study of freezetolerant and anoxia-tolerant wood frogs, Rana sylvatica, showed that anoxia exposure induced a significant decrease in critical cell cycle components (type D1 and E1 cyclins, type 2, 4 and 6 cyclindependent kinases) as well as an increase in cell cycle inhibitors (p16 INK4A and p27…”
Section: Introductionmentioning
confidence: 99%
“…but, on the molecular scale, many intracellular energy‐expensive enzymes, pathways and functions are specifically targeted and strongly suppressed (Storey and Storey, 2004b, 2007). One of the most energy‐expensive activities that organisms undertake is the proliferation of cells to support growth or development and to replace damaged cells (Mazia, '62). Therefore, we hypothesized that cell cycle arrest would be a very important component of global metabolic rate depression as a survival strategy for dealing with anoxia or dehydration stresses.…”
mentioning
confidence: 99%